The Effect of Halal Certification and Halal Awareness through Interest in Decisions on Buying Halal Food Products - Eka Dyah Setyaningsih; Sofyan Marwansyah (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2019)
This study aims to examine the effect of halal certification and halal awareness through interest in consumer decisions in buying food products. The sample of this study is consumers who live in the area of Jakarta and Bogor with 350 respondents. The sampling technique used with snowball sampling. Data analysis using Structural Equation Modeling (SEM) which is run with AMOS software is used to analyze data. The results of the analysis show that halal certification and halal awareness have a positive effect on consumer decisions. The results of the study indicate that halal certification has a significant effect on consumer interest with a correlation value of 0.246; halal awareness has a positive effect on customer decisions with a correlation value of 0.208; service quality has a positive effect on customer decisions with a correlation value of 0.180